Characterization of biopolymer Blend-based on alginate and Poly(vinyl Alcohol) as an application for polymer host in polymer electrolyte - N. M., Ghazali; N. F., Mazuki; A. S., Samsudin (Elsevier Ltd, 2021)
In the present work, alginate (Alg) blend with polyvinyl alcohol (PVA) with various compositions was prepared by using solution casting method. The intermolecular interaction occurred in the polymer blends were investigated via Fourier Transform Infrared (FTIR) spectroscopy. Electrical impedance spectroscopy was used to determine the conductivity values of the blends. The conductivity value of Alg-PVA polymer blend was found to be optimum at (7.52 ± 0.04) × 10−8 S/cm for composition with 70:30 of Alg:PVA. Based on the findings, it is believed that the Alg-PVA blend is a promising candidate to be act as polymer host materials for application in polymer electrolyte system.